ACR Appropriateness Criteria® Pretreatment Staging of Colorectal Cancer - Fowler, Kathryn J.; Kaur, Harmeet; Cash, Brooks D.; Feig, Barry W.; Gage, Kenneth L.; Garcia, Evelyn M.; Hara, Amy K.; Herman, Joseph M.; Kim, David H.; Lambert, Drew L.; Levy, Angela D.; Peterson, Christine M.; et al. (Journal of the American College of Radiology, 2017)
Colorectal cancers are common tumors in the United States and appropriate imaging is essential to direct appropriate care. Staging and treatment differs between tumors arising in the colon versus the rectum. Local staging for colon cancer is less integral to directing therapy given radical resection is often standard. Surgical options for rectal carcinoma are more varied and rely on accurate assessment of the sphincter, circumferential resection margins, and peritoneal reflection. These important anatomic landmarks are best appreciated on high-resolution imaging with transrectal ultrasound or MRI. When metastatic disease is suspected, imaging modalities that provide a global view of the body, such as CT with contrast or PET/CT may be indicated. Rectal cancer often metastasizes to the liver and so MRI of the liver with and without contrast provides accurate staging for liver metastases. This article focuses on local and distant staging and reviews the appropriateness of different imaging for both variants. The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment.